Amino group-rich porous g-C3N4 nanosheet photocatalyst: Facile oxalic acid-induced synthesis and improved H2-evolution activity. Issue 13 (1st July 2021) - Zhao, Binbin; Xu, Jiachao; Liu, Yongping; Fan, Jiajie; Yu, Huogen
Abstract: The reasonable modulation of tri- s -triazine structure units of g-C3 N4 is an effective method to optimize its intrinsic electronic and optical properties, thus boosting its photocatalytic hydrogen-evolution activity. Herein, amino groups are successfully introduced into the tri- s -triazine structure units of g-C3 N4 nanosheets to improve their H2 -evolution activity via a facile oxalic acid-induced supramolecular assembly strategy. In this case, the resulting amino group-rich porous g-C3 N4 nanosheets display a loose and fluffy structure with a large specific surface area (70.41 m 2 g −1 ) and pore volume (0.50 cm 3 ⁠ g −⁠1 ), and enhanced visible-light absorption (450–800 nm). Photocatalytic tests reveal that the amino group-rich porous g-C3 N4 nanosheets (AP-CN1.0 nanosheets) exhibit a significantly elevated photocatalytic H2 -production activity (130.7 μmol h −1, AQE = 5.58%), which is much greater than that of bulk g-C3 N4 by a factor of 4.9 times. The enhanced hydrogen-generation performance of amino group-rich porous g-C3 N4 nanosheets can be mainly attributed to the introduction of more amino groups, which can reinforce the visible-light absorption and work as the interfacial hydrogen-generation active centers to boost the photocatalytic hydrogen production. The present facile and effective regulation of tri- s -triazine structure units may provide an ideal route for the exploitation of novel and highly efficient g-C3 N4 photocatalysts.